Aminoethylimidazole ionic liquid-grafted MIL-101-NH2 heterogeneous catalyst for the conversion of CO2 and epoxide without solvent and cocatalyst. (16th July 2021) - Bao, Chenglong; Jiang, Yichen; Zhao, Liyan; Li, Dazhi; Xu, Ping; Sun, Jianmin
Abstract : An aminoethylimidazole IL-functionalized MIL-101-NHIM-NH2 catalyst efficiently catalyzes the cycloaddition reaction of CO2 and epoxide without solvent and cocatalyst, owing to the synergistic effects of Cr, –NH2 and Br − active sites. Abstract : Besides the activation of CO2 by Lewis basic groups, the synergistic effects of Lewis acid sites (or hydrogen bond donor) together with halogen nucleophilic anions to activate epoxide ring opening were also important steps to develop an efficient catalyst for the cycloaddition reaction of CO2 and epoxides. Herein, an aminoethylimidazole IL-modified MOF catalyst with multiple catalytic active sites (denoted as MIL-101-NHIM-NH2 ) was synthesized through an aldimine condensation post-synthesis method. Through thorough characterizations, such as FT-IR, XRD, SEM-EDS mappings, N2 adsorption and desorption, XPS, elemental analysis and TG measurement, the results showed that the surface of MIL-101-NHIM-NH2 was successfully grafted with the ionic liquid. Owing to the synergistic effects of multiple active sites containing Cr, –NH2 and Br − in the MIL-101-NHIM-NH2 catalyst, MIL-101-NHIM-NH2 could efficiently catalyze the cycloaddition reaction of CO2 and epoxide without additional solvent and cocatalyst; 93.5% of propylene carbonate was obtained at 120 °C, 2 MPa and 4 h. Moreover, MIL-101-NHIM-NH2 also showed better recycling stability within five catalytic runs and easy separation in the CO2 cycloaddition reaction.